Eight Months Later: A Family Case Study of L2 Acquisition of English Morphology - Yanyin Zhang; Ima Widyastuti (TAMANSISWA INTERNATIONAL JOURNAL IN EDUCATION AND SCIENCE, 2020)
This is a follow-up of our 2010 family case study (Zhang & Widyastuti, 2010)in which we examined the acquisition of L2 English morphology by three members of an Indonesian family who had been living, working and studying in Australia for 12 months. In this paper, we will present a fresh set of data collected after a further 8 months in order to build a longitudinal picture of their L2 English morphology development. We will focus on the Mother and her 6-year-old Daughter, whose L2 English morphology, in 2010, was found to be at the beginning and post-beginning stages as measured by the ‘emergence criterion’ (Pienemann, 1998). We are interested in the extent of progress they had made since, and whether the L2 English grammatical morphology had been fully established by the end of their 20 months of residence in Australia. Our analysis of their speech data showed that while there was indeed progress, the progress was not comprehensive and the acquisition was incomplete. We discuss the finding from the perspective of immersion, home environment, and affective factors in L2 grammatical development, in particularly, in child L2 learners. The results of the study may inform language professionals and parents of young child L2 learners of the lengthy period required as well as the type of optimal L2 environment for their L2 grammatical development.